Perlindungan Hukum Terhadap Korban Tindak Pidana Penghinaan Citra Tubuh (Body Shaming) - Ni Made Yeni Sukmawati; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
Body Shaming is a term that is currently trending, where criticizing or commenting on someone's physical in a negative way or with speech that intends to mock or insult someone's physical or appearance falls into this category. Legal protection for victims of body shaming needs to get very serious attention in order to deal with the phenomena that are currently happening on social media in particular. This study examines the regulation of the criminal act of insulting body image (body shaming) in terms of positive law and explains the legal protection provided to victims in the crime of insulting body image (body shaming). This study uses a normative research method by applying the legislation approach which refers to primary legal materials and secondary legal materials. The regulation of criminal acts of insulting body image (body shaming) in terms of positive law in general can be seen from the element of humiliation which is regulated in Chapter XVI of the Criminal Code and is grouped into 6 parts, namely from article 310 to article 318 and besides that, there are also other legal rules that regulate it implicitly in Article 27 paragraph (3). Article 45 paragraph (3) of the ITE Law. With sanctions in the form of criminal sanctions. The form of legal protection given to victims in the crime of body shaming is the making of policies by the State regarding prohibitions and strict sanctions for violators such as criminal sanctions and fines, through the established witness and victim protection institution